2001
DOI: 10.1046/j.1365-2281.2001.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation–perfusion inequality and carbon dioxide sensitivity in hypoxaemic chronic obstructive pulmonary disease (COPD) and effects of 6 months of long‐term oxygen treatment (LTOT)

Abstract: An elevated V mean and probably shunting are important contributing factors for the reduced PaO(2) and hypercapnic ventilatory response is a major determinant of PaCO(2) in eucapnic stable hypoxaemic COPD. Six months of LTOT does not affect blood gases, CO(2) sensitivity or ventilation-perfusion relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…These results are considered to be due to larger variation of V/Q in more advanced staging of emphysema, and these parameters appear adequate to evaluate the severity of lung V-Q imbalance in patients with emphysema. The previous studies showed that lung gas diffusing capacity was more severely disturbed in advanced stage of chronic obstructive pulmonary diseases [4,16]. As SD of V/Q profile was significantly correlated with A-aDO2 in our patients, it can be a good parameter to evaluate the severity of lung gasexchange impairment in patients with emphysema.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…These results are considered to be due to larger variation of V/Q in more advanced staging of emphysema, and these parameters appear adequate to evaluate the severity of lung V-Q imbalance in patients with emphysema. The previous studies showed that lung gas diffusing capacity was more severely disturbed in advanced stage of chronic obstructive pulmonary diseases [4,16]. As SD of V/Q profile was significantly correlated with A-aDO2 in our patients, it can be a good parameter to evaluate the severity of lung gasexchange impairment in patients with emphysema.…”
Section: Discussionsupporting
confidence: 55%
“…Regional lung V-Q balance in patients with emphysema should be variously impaired according to the degree of alveolar destruction, airway obstruction, increased lung tissue compliance, air trapping, hyperinflation and resultant compression of bronchioles or small vasculatures, collateral ventilation, and hypoxic vasoconstriction associated with ventilation disturbance [4,[15][16][17][18][19]. Cigarette smoking usually and initially induces inflammatory obstruction of airflow in central and/or peripheral airways, and subsequently induces alveolar destruction [15][16][17][18][19][24][25][26]. Lungs in smokers may have partial lung areas with airway obstruction but without significant alveolar interstitial microvascular destruction, where ventilation may be more disturbed compared with perfusion, resulting in shunt effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In emphysema, a high V/Q ratio, caused by increased physiological dead space due to the destruction of the pulmonary capillary bed, is predominant (20). In a study of 14 patients with severe or very severe COPD, V/Q mismatch was found to be the most important cause of hypoxaemia through 'wasted' ventilation of poorly perfused areas (21). Also, low V/Q ratios can be present in emphysema.…”
Section: Discussionmentioning
confidence: 99%